Status Kepemilikan Tanah Hasil Konversi Hak Barat Berdasarkan UU NO. 5 Tahun 1960 - Ulfia Hasanah (Fakultas Hukum Universitas Riau, 2012)
With the enactment of Law No. 5 of 1960 concerningthe Basic Agrarian fundamental changes to the agrar-ian law in Indonesia, especially in the area of land.As for the legal basis for the conversion of land rightsis the second part of the Act concerning the provisionsof the conversion consists of nine chapters that gov-ern the conversion of three types, namely: the conver-sion of land resulting from Indonesia’s rights, con-version rights to land former Autonomous and con-version of land rights from the rights of the west.